2015
DOI: 10.1182/blood-2015-04-638528
|View full text |Cite
|
Sign up to set email alerts
|

2p15-p16.1 microdeletions encompassing and proximal to BCL11A are associated with elevated HbF in addition to neurologic impairment

Abstract: Key Points Elevation of HbF in 3 patients heterozygous for distinct 2p15-p16.1 syndrome microdeletions affecting BCL11A. Identification of novel, putative regulatory elements downstream of BCL11A that govern its expression in erythroid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…All of the patients had substantial persistence of HbF ranging between 15-30% in the setting of BCL11A mRNA haploinsufficiency, without observable abnormalities in either other blood or immune cell phenotypes. Similar findings have also been reported in subsequent follow-up studies (41). Importantly, we could demonstrate using a variety of orthogonal genetic datasets that BCL11A had a key role in human neurodevelopment, suggesting the importance of careful phenotypic assessment with any potential BCL11A-targeting therapies that may be developed in the future (40).…”
Section: Fetal Hemoglobin Regulation and Variation In The Hemoglobinsupporting
confidence: 86%
“…All of the patients had substantial persistence of HbF ranging between 15-30% in the setting of BCL11A mRNA haploinsufficiency, without observable abnormalities in either other blood or immune cell phenotypes. Similar findings have also been reported in subsequent follow-up studies (41). Importantly, we could demonstrate using a variety of orthogonal genetic datasets that BCL11A had a key role in human neurodevelopment, suggesting the importance of careful phenotypic assessment with any potential BCL11A-targeting therapies that may be developed in the future (40).…”
Section: Fetal Hemoglobin Regulation and Variation In The Hemoglobinsupporting
confidence: 86%
“…This raises the issue of safety in terms of neurogenesis, because patients with deletions in BCL11A appear prone to schizophrenia and autism spectrum disorders. 40,41 However, in preliminary studies, pomalidomide was added to human neuronal cell lines, and there was no change in the expression levels of BCL11A (supplemental Figure 6). In addition, pomalidomide induces less neuropathy than thalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with missense and LoF mutations (Dias et al, 2016), or BCL11A encompassing 2p15p16 microdeletions (Basak et al, 2015; Funnell et al, 2015) were shown to have elevated fetal hemoglobin levels, ranging from 3.1% (Dias et al, 2016) to 29.7% (Basak et al, 2015). Our patient value of 4.5% of HbF is thus in accordance with reported cases and constitutes additional evidence for the pathogenic nature of the LoF variant observed in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…BCL11A has been shown to be a critical modulator of hemoglobin switching and HbF silencing (Basak et al, 2015; Funnell et al, 2015; Guda et al, 2015; Xu et al, 2013). In the murine brain, Bcl11a controls cell polarity, radial migration of upper cortical neurons, axon branching, and dendrite outgrowth (Kuo, Chen, & Hsueh 2010; Kuo, Hong, & Hsueh, 2009; Kuo, Hong, Chien, & Hsueh, 2010; Wiegreffe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation